2013
DOI: 10.1007/s12033-013-9709-x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Heterologous Expression, Purification and Characterization of M12 Mutant of Aspergillus niger Glucose Oxidase in Yeast Pichia pastoris KM71H

Abstract: Aspergillus niger glucose oxidase (GOx) genes for wild-type (GenBank accession no. X16061, swiss-Prot; P13006) and M12 mutant (N2Y, K13E, T30 V, I94 V, K152R) were cloned into pPICZαA vector for expression in Pichia pastoris KM71H strain. The highest expression level of 17.5 U/mL of fermentation media was obtained in 0.5 % (v/v) methanol after 9 days of fermentation. The recombinant GOx was purified by cross-flow ultrafiltration using membranes of 30 kDa molecular cutoff and DEAE ion-exchange chromatography at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…There was excellent stability, substrate affinity and catalytic activity perceived in the two enzymes purified has shown that these enzymes can be used in industrial applications as well as in biosensors. The GODs extracted and purified from naturally isolated strains displayed optimum activity at lower temperature than GOD from Aspergillus tubingensis and a recombinant GOD from Penicillium amagasakiense 16,17 .The Km of the GOD from both the isolated strain was similar to the Km and Vmax of GOD from A. niger, and Penicillium species a recombinant one expressed in Pichia pastoris 16,18,19 . Inhibition of the enzyme activity by chemical agents such as chelating and denaturing agents along with substrates were similar to Aspergillus niger.…”
Section: Resultsmentioning
confidence: 90%
“…There was excellent stability, substrate affinity and catalytic activity perceived in the two enzymes purified has shown that these enzymes can be used in industrial applications as well as in biosensors. The GODs extracted and purified from naturally isolated strains displayed optimum activity at lower temperature than GOD from Aspergillus tubingensis and a recombinant GOD from Penicillium amagasakiense 16,17 .The Km of the GOD from both the isolated strain was similar to the Km and Vmax of GOD from A. niger, and Penicillium species a recombinant one expressed in Pichia pastoris 16,18,19 . Inhibition of the enzyme activity by chemical agents such as chelating and denaturing agents along with substrates were similar to Aspergillus niger.…”
Section: Resultsmentioning
confidence: 90%
“…After that, the total enzyme yield and wet cell mass tended to decrease, and the methanol consumption rate apparently reduced, which implied the deadline of fermentation. The maximal enzymatic activity of GOxP 5 in shake flask was much higher than many heterologously expressed enzymes in P. pastoris, such as GOx form P. variable (0.33 U/mL), A. niger (1.23 U/mL), and A. niger NRLL-3 (17.5 U/mL) (Kalisz et al, 1997;Yamaguchi et al, 2007;Kovačević et al, 2014). Although the highest expression level of GOxP 5 in P. pastoris after high-cell-density fermentation was lower than that of GOD-m from Penicillium notatum (615 U/mL) (Gao et al, 2012), it was still of great value due to its excellent characteristics in food preservation area.…”
Section: Discussionmentioning
confidence: 91%
“…Crognale et al (2006) described a genetically modified P. pastoris X 33 with the gene encoding the GOX from P. variabile P16, and the activity only reached at 50 U/mL. Kovačević et al (2014) cloned several mutated glucose oxidase genes from A. niger M12 and expressed them in P. pastoris KM71H. The highest activity of the GOD came up to 17.5 U/mL of fermentation media.…”
Section: Discussionmentioning
confidence: 99%